ANALISIS KINERJA ORGANISASI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL DALAM MEMBERIKAN PELAYANAN PEMBUATAN KARTU IDENTITAS ANAK (KIA) DI KOTA SEMARANG - Salsabila Diyamarsis, Cika; Nurcahyanto, Herbasuki; Marom, Aufarul (Journal of Public Policy and Management Review, 2024)
KIA (Kartu Identitas Anak) is a population identity to improve data collection, protection and convenience in providing public services to children in order to realize the best rights of children with the implementing agency being the Department of Population and Civil Registration. KIA has been in effect since 2016 and is regulated by the Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 2 of 2016. In Semarang City, KIA ownership has never reached the expected target. This is the problem behind this research which aims to analyze the organizational performance of the Semarang City Population and Civil Registration Service in providing services for making KIA and identify factors that support and inhibit organizational performance at the City Population and Civil Registration Service Semarang in providing services for making KIA. Then this research uses a qualitative descriptive approach with data collection techniques, namely interviews, observation and documentation. The theory used in this research is Dwiyanto's theory with the research phenomena of productivity, service quality, responsiveness, responsibility and accountability. The research results show that the research phenomenon studied is still not optimal. Supporting factors for the organizational performance of the Semarang City Population and Civil Registration Service in KIA production services are leadership factors and team factors. Meanwhile, the factors inhibiting organizational performance are system factors and situational/contextual factors.